Nonstandard additively finite triangulated categories of Calabi-Yau dimension one in characteristic 3 - Bialkowski, J.; Skowronski, A. (Algebra and Discrete Mathematics, 2007)
We prove that there exist nonstandard K-linear triangulated categories with finitely many indecomposable objects and Calabi-Yau dimension one over an arbitrary algebraically closed field K of characteristic 3, using deformed preprojective algebras of generalized Dynkin type.